Dynamic Jumping - King, M.
The performance of dynamic jumps is the result of complex interactions between many factors, including preflight characteristics, muscle strength and activation timings, and the elastic properties of external contact surfaces. Much of the work carried out at Loughborough aims to determine the contributions of these factors to the performance of dynamic jumps and to gain a greater understanding of the underlying mechanics. Theoretical computer simulation models were developed incorporating muscle representations and elastic interfaces between the model and the external contact surfaces for vaulting and tumbling takeoffs in gymnastics. The simulation models were customised to represent the elite male gymnast analysed in this study by calculating subject specific inertia and muscle parameters from experimental testing with the gymnast. The simulation models were evaluated by comparing simulations of each movement with actual vaulting and tumbling performances by the elite male gymnast and then used to quantify the contributions to vaulting and tumbling performance. The characteristics of the preflight were found to have a major influence on both vaulting and tumbling performance. In addition, for tumbling, the takeoff strategy (activation timings of the muscles) was also crucial, with it being possible to produce a range of postflight performances by just changing the strategy used during the takeoff. Vaulting and tumbling performances were found to be relatively insensitive to changes (within realistic limits) in the elastic nature of the contact surfaces and for vaulting the elasticity of the the hand / foot was found to prolong the duration of contact with an external surface.